2014
DOI: 10.1155/2014/285857
|View full text |Cite
|
Sign up to set email alerts
|

Noncovalent Attachment of PbS Quantum Dots to Single- and Multiwalled Carbon Nanotubes

Abstract: Attachment of PbS quantum dots (QD) to single-walled carbon nanotubes (SWNT) and multiwalled carbon nanotubes (MWCNT) is described; wherein commercially obtained PbS-QD of size 2.7 nm, stabilized by oleic acid, are added to a suspension of single- or multiwalled carbon nanotubes (CNT) prefunctionalized noncovalently with 1,2-benzenedimethanethiol (1,2-BDMT) in ethanol. The aromatic part of 1,2-BDMT attaches to the CNT byπ-πstacking interactions, noncovalently functionalizing the CNT. The thiol part of the 1,2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Nevertheless, when simple physical mixing is applied long deposition times, low photocurrents due to the isolating effect of the ligands and inefficient deposition of QDs on CNTs backbone is the minimum shortcomings of this approach. Das et al, [133] proposed a method for the attachment of commercially obtained oleic acid stabilized monodispersed PbS QD with the size of 2.7 nm onto the surface of CNT prefunctionalized by an aromatic dithiol (1,2-BDMT). They believed that the aromatic part of 1,2-BDMT attaches to the CNT by π-π stacking interactions and the thiol part replaces oleic acid on the surface of QDs, leading to the non-covalent attachment of the QD to the CNT.…”
Section: Hybrid Solar Cells Based On Cnt Decorated With Qd Nanostructmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, when simple physical mixing is applied long deposition times, low photocurrents due to the isolating effect of the ligands and inefficient deposition of QDs on CNTs backbone is the minimum shortcomings of this approach. Das et al, [133] proposed a method for the attachment of commercially obtained oleic acid stabilized monodispersed PbS QD with the size of 2.7 nm onto the surface of CNT prefunctionalized by an aromatic dithiol (1,2-BDMT). They believed that the aromatic part of 1,2-BDMT attaches to the CNT by π-π stacking interactions and the thiol part replaces oleic acid on the surface of QDs, leading to the non-covalent attachment of the QD to the CNT.…”
Section: Hybrid Solar Cells Based On Cnt Decorated With Qd Nanostructmentioning
confidence: 99%
“…However, in this approach controlled deposition of QDs is complicated and agglomeration is inevitable. Consequently, covalent functionalization of CNT [133], QDs [16] or both of these two nanomaterial's [22] has been studied. Cho et al [134] have shown that by thiol covalent modification of SWNT, a large number of PbSe QDs are attached on the surface of CNT.…”
Section: Hybrid Solar Cells Based On Cnt Decorated With Qd Nanostructmentioning
confidence: 99%
“…Conjunction: Conjunction, which can be grouped into two general strategies: noncovalent coupling [38] and covalent coupling [39,40], is a common fabrication method. Some functional QDs have been fabricated by noncovalent coupling such as electrostatic interactions [20] or π-π stacking interactions [31].…”
Section: Synthesis Protocolsmentioning
confidence: 99%
“…To fabricate the functional QDs, other intermediate molecules including 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) and/ or N-hydroxysuccinimide (NHS) have been involved [6,11,38]. QDs were first covalently coupled with aptamer specific for mutated MUC1 mucin overexpressed in ovarian carcinoma cells, followed by doxorubicin covalently coupled with QDs -MUC1 aptamer conjugates by EDC and NHS [6].…”
Section: Synthesis Protocolsmentioning
confidence: 99%
“…[Vilatela and Eder 2012;Eder 2010;Shearer et al 2014] In the ex-situ route, also known as the building block approach, the two components are synthesised separately and then attached using covalent, non-covalent or electrostatic interactions (Figure 2.4). This strategy has been used to successfully link nanoparticles [Yeh et al 2009], quantum dots [Das et al 2014], polymers [Gegenhuber et al 2015] and biomolecules, especially proteins [Kuila et al 2010]. In contrast, in the in-situ route, one component of the hybrid is synthesised in presence of the other or sometimes both are synthesised at the same time.…”
Section: Nanocarbon-based Hybridsmentioning
confidence: 99%